An Alternative Explanation for the Resource Curse : The Income Effect Channel - Alichi, Ali (IMF Working Papers; Working Paper, 2009)
The paper provides an alternative explanation for the "resource curse" based on the income effect resulting from high government current spending in resource rich economies. Using a simple life cycle framework, we show that private investment in the non-resource sector is adversely affected if private agents expect extra government current spending financed through resource sector revenues in the future. This income channel of the resource curse is stronger for countries with lower degrees of openness and forward altruism. We empirically validate these findings by estimating non-hydrocarbon sector growth regressions using a panel of 25 oil-exporting countries over 1992-2005.